Fratura de ângulo de mandíbula: avaliação do comportamento mecânico do osso variando o material para fixação (TiCP e Ti-Mo) e a técnica de fixação interna rígida (Champy e AO/ASIF), com o método dos elementos finitos tridimensional - Oliveira, Gustavo Barbosa de [UNESP] (2013)
The aim of this study was to analyze the mechanical behavior of bone after simulation of fracture of the mandibular angle and rigid internal fixation using plates and screws made from commercially pure titanium (TiCP) and an experimental titanium- molybdenum alloy (Ti-Mo). In addition, two rigid internal fixation techniques were analyzed: Champy technique and AO/ASIF technique. The tomographic image from a radiopaque physical replica of the mandible was used to generate a geometric model similar to the physical replica with Mimics software. The plates and screws were modeled in the graphic design program SolidWorks v.2009 and adapted to the mandible. Thus, 4 geometric models representing part of the mandibular body, ramus, and mandibular angle with the fracture fixed with plates and screws were specify the following groups: group 1 - a segment of the mandibular angle fractured, with internal fixation by Champy technique, using plates and screws of commercially pure titanium (Ti-CP), group 2 - a segment of the mandibular angle fractured, with internal fixation by Champy technique, using a plate and screws of experimental titanium-based molybdenum alloy (Ti-Mo), group 3 - a segment of the mandibular angle fractured, with internal fixation by Association Osteosynthesis/Association for the Study of Internal Fixation (AO/ASIF) technique, using plate and screws of commercially pure titanium (Ti-CP), group 4 - a segment of the mandibular angle fractured, with rigid internal fixation by AO/ASIF technique, using plate and screws of experimental titanium-molybdenum alloy (Ti-Mo). In all simulations, the cross-sectional area of the ramus was fixed in the x, y and z axes (x = y = z = 0). A distributed load of 200N was applied to the occlusal surface of a mandibular first molar. The numerical analysis was performed using the finite element software, Ansys Workbench 10.0. The results...